2014
DOI: 10.4103/0973-029x.151313
|View full text |Cite
|
Sign up to set email alerts
|

Detection of salivary interleukin-2 in recurrent aphthous stomatitis

Abstract: Objective:The present study was undertaken to estimate and compare salivary interleukin-2 (IL-2) levels in patients with recurrent aphthous stomatitis, among healthy controls and their variation with age and sex.Study Design:Saliva was collected from 60 patients within the age range of 16-60 years which included 30 patients (17 Females and 13 Males) with recurrent aphthous stomatitis and healthy control group consisted of 30 participants (18 Females and 12 Males). IL-2 estimation was done in both the groups us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Table 1 shows the characteristics of the researched studies based on the examination of interleukin levels. Two articles showed that the research conducted in India [18,21], two articles in Turkey [19,25], three articles in Iran [22][23][24], and one article in China [20]. The number of research subjects in each article consists of 25 to 184 RAS patients, or 551 patients with RAS diagnoses in total.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the characteristics of the researched studies based on the examination of interleukin levels. Two articles showed that the research conducted in India [18,21], two articles in Turkey [19,25], three articles in Iran [22][23][24], and one article in China [20]. The number of research subjects in each article consists of 25 to 184 RAS patients, or 551 patients with RAS diagnoses in total.…”
Section: Resultsmentioning
confidence: 99%
“…Increased salivary levels of IL‐2, one of the proinflammatory cytokines produced by T‐helper (Th)1 cells, were found in patients with RAS compared with healthy controls . While no statistical differences were observed in the serum levels of IL‐2 between patients with RAS and controls in a Turkish population , Sun et al .…”
Section: Discussionmentioning
confidence: 98%
“…Increased salivary levels of IL-2, one of the proinflammatory cytokines produced by T-helper (Th)1 cells, were found in patients with RAS compared with healthy controls (36). While no statistical differences were observed in the serum levels of IL-2 between patients with RAS and controls in a Turkish population (37), SUN et al (26) suggested that the markedly increased plasma level of IL-2 may have resulted from secretion by the increased number of activated CD4 + cells and that the expression of IL-2R by activated peripheral blood lymphocytes was upregulated by the plasma level of IL-2 in patients with RAS.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the limited availability of preventative or therapeutic options for recurrent aphthous stomatitis results from poor understanding of its etiopathogenic process 10 , and the stagnation in our understanding of the condition over the last few decades. One of the biggest problems is that the scientific focus has been on studying individual molecules, such as TNF-α 11 , IL-2 12 , and cortisol 13 . In addition, much of the published research has not evaluated sample sets representing the clinical course of the disease.…”
Section: Introductionmentioning
confidence: 99%